Detoxification of Implant Surfaces Affected by Peri-Implant Disease: An Overview of Surgical Methods - Pilar Valderrama; Thomas G. Wilson Jr (International Journal of Dentistry)
Purpose. Peri-implantitis is one of the major causes of implant failure. The detoxification of the implant surface is necessary to obtain reosseointegration. The aim of this review was to summarize in vitro and in vivo studies as well as clinical trials that have evaluated surgical approaches for detoxification of the implant body surfaces. Materials and Methods. A literature search was conducted using MEDLINE (PubMed) from 1966 to 2013. The outcome variables were the ability of the therapeutic method to eliminate the biofilm and endotoxins from the implant surface, the changes in clinical parameters, radiographic bone fill, and histological reosseointegration. Results. From 574 articles found, 76 were analyzed. The findings, advantages, and disadvantages of using mechanical, chemical methods and lasers are discussed. Conclusions. Complete elimination of the biofilms is difficult to achieve. All therapies induce changes of the chemical and physical properties of the implant surface. Partial reosseointegration after detoxification has been reported in animals. Combination protocols for surgical treatment of peri-implantitis in humans have shown some positive clinical and radiographic results, but long-term evaluation to evaluate the validity and reliability of the techniques is needed.